2018
DOI: 10.4172/2157-7439.1000487
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Selenium Nanoparticles

Abstract: Nanomedicine & Nanotechnology J o ur nal of N a n o m ed icine & N a n o te chnolo g y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…The results of the present study indicated that SeNPs are of beneficial effects on liver functions and restored the activities of ALT and AST toward normal levels as well as the level of albumin. These finding could be explained due to the radical scavenging property of Se and the importance of Se in protecting the integrity and the functions of tissues (Majeed et al 2018). These results could be due to the role of SeNPs in protecting the integrity and functions of liver tissues besides its radical scavenging activity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of the present study indicated that SeNPs are of beneficial effects on liver functions and restored the activities of ALT and AST toward normal levels as well as the level of albumin. These finding could be explained due to the radical scavenging property of Se and the importance of Se in protecting the integrity and the functions of tissues (Majeed et al 2018). These results could be due to the role of SeNPs in protecting the integrity and functions of liver tissues besides its radical scavenging activity.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have shown that SeNPs downregulate mRNA expression of pro-inflammatory cytokines including inducible NO synthase (iNOS), interleukin IL-1, and TNF-α thus reducing inflammation (Shi et al 2011;Wang et al 2016). Selenium is known as a fundamental component of selenoprotein, an essential enzyme in the body that protects against oxidative stress and inflammation (Majeed et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Se supplementation improves the condition of patients as well as reduces inflammation levels in experimental models, such as the granuloma pouch exudate, and in lupus mice or in the adjuvant arthritis in rats [ 41 ]. Evidence has suggested that Se can decrease inflammation in autoimmune disorders [ 42 ]. One report revealed that Se supplementation has an antioxidant effect as it upregulates selenoproteins and downregulates inflammation in autoimmune disorders [ 43 ].…”
Section: Serum Selenium Status In Rheumatoid Arthritismentioning
confidence: 99%
“…SeNPs can be synthesized via physical techniques such as UV radiation and laser ablation; chemically via acid decomposition, catalytic reductions, and precipitation, biologically via microorganisms or plant extracts [11]. The health benefi ts of SeNPs are anti-aging, antioxidant, antidiabetic, boost immunity, reduces infl ammation, improves fertility and brain functions, anti-asthma, anti-arthritic, treats muscular dystrophy, antiviral, and regulates thyroid [12].…”
Section: Introductionmentioning
confidence: 99%